1999
DOI: 10.1007/pl00006445
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Assessment of the Eukaryotic Light-Harvesting Antenna Proteins, with Implications for Plastid Evolution

Abstract: The light-harvesting complexes (LHCs) are a superfamily of chlorophyll-binding proteins present in all photosynthetic eukaryotes. The Lhc genes are nuclear-encoded, yet the pigment-protein complexes are localized to the thylakoid membrane and provide a marker to follow the evolutionary paths of plastids with different pigmentation. The LHCs are divided into the chlorophyll a/b-binding proteins of the green algae, euglenoids, and higher plants and the chlorophyll a/c-binding proteins of various algal taxa. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
158
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(170 citation statements)
references
References 38 publications
(43 reference statements)
10
158
1
Order By: Relevance
“…Sequencing showed that they were indeed members of the LHC superfamily, even though they bound only Chl a and were associated only with photosystem I (6 -8). This showed that phycobilisomes (associated primarily with PSII) and membrane-intrinsic antennas of the LHC superfamily could coexist in the same chloroplast, and strongly supported a common evolutionary origin for all chloroplasts (8). In addition, it suggested that ancestral members of the LHC family may have had a considerable degree of f lexibility in pigment binding, so they were able to adapt to binding a variety of different Chls and carotenoids.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Sequencing showed that they were indeed members of the LHC superfamily, even though they bound only Chl a and were associated only with photosystem I (6 -8). This showed that phycobilisomes (associated primarily with PSII) and membrane-intrinsic antennas of the LHC superfamily could coexist in the same chloroplast, and strongly supported a common evolutionary origin for all chloroplasts (8). In addition, it suggested that ancestral members of the LHC family may have had a considerable degree of f lexibility in pigment binding, so they were able to adapt to binding a variety of different Chls and carotenoids.…”
mentioning
confidence: 73%
“…These features might be expected to impede the binding of Chl c to a Chl a site and even diminish protein folding, but this was not found in the experiments of Grabowski et al (9). All of these experiments suggest that the differences in sequence among the LHC proteins (8) optimizing energy transfer, binding carotenoids, and forming protein-protein interactions than with binding a specific Chl.…”
mentioning
confidence: 99%
“…Heinemann and Paulsen (38) showed that a point mutation in such a domain of LHCII abolished in vitro reconstitution, suggesting that it is critical for assembly of a functional complex possibly because carotenoid binding cannot occur. However, conservation of the putative carotenoid binding sites is not consistent across taxa (11,39). In any case, it is difficult to imagine how these putative carotenoid binding sites could accommodate eight or more carotenoid molecules in one LHC polypeptide.…”
Section: A Simple Red Algal Lhc Protein Binds All Major Chlorophylls Andmentioning
confidence: 99%
“…The LHCs of the red alga P. cruentum (LhcaR1, LhcaR2) are similar in sequence and predicted structure to LHCs of green plants and of other algae (6, 10), but phylogenetic analyses suggest a closer phylogenetic affinity with LHCs of chromophytes and dinophytes than with those of chlorophytes (11). Three transmembrane helices are a common feature of most LHCs, with eight conserved Chl-binding sites in chromophytes, dinophytes, and rhodophytes (6,10,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation